Effect of Using Audiovisual Learning Media Based on the Canva Application on Students Science Learning Outcomes - Nurul Husna; Sauqina Sauqina; Yasmine Khairunnisa (Jurnal Pijar MIPA, 2026)
In response to the growing need for innovative and technology-integrated instructional strategies in science education. This study aims to analyze the effect of using the Canva application-based audiovisual learning media on the science learning outcomes of seventh-grade students on the material of changes in the state of matter. The method applied is a quasi-experiment with a nonequivalent control group design. The population includes all seventh-grade students of SMP Negeri 1 Banjarmasin. Through convenience sampling, a research sample of 60 people was obtained: 30 in class VII D (control) and 30 in class VII E (experimental). Data were collected through a validated, reliable learning outcome test. The data analysis techniques used in this study include calculating averages and standard deviations, performing normality and homogeneity tests, and conducting hypothesis tests. Hypothesis testing in this study was conducted using ANCOVA (Analysis of Covariance). The results of the hypothesis test showed a Sig. value of 0.001 <0.05, with an effect size of 0.171, which is classified as a small category. Therefore, the decision was made to reject H0 and accept H1. The conclusion of this study is that the use of audiovisual learning media in the Canva application affects the science learning outcomes of grade VII students on the material on changes in state of matter.